TECHNOLOGICAL STANDARDS ASA MEANS OF PROVIDING QUALITYSERVICES OF E-LEARNING - Kistaman T. Magomedova (Статистика и экономика, 2016)
Article about history of development of technological standards and e-learning forms, conducted a parallel between them and showing their relationship. It is shown that for the provision of quality services in the e-learning, you must have the actual standards that meet the requirements of modern trends.